Perbedaan Nilai Arus Puncak Ekspirasi Pada Laki-Laki Antara Pekerja Pabrik Kayu Dan Pekerja Kantoran Di Sukoharjo - Nurhidayat, Imam, Dr. Sri Wahyu Basuk.,M.Kes (2017)
Dust exposure in the work environment may cause changes in physiology and disorders of the respiratory system. Factory workers who exposed to dust have low peak expiratory flow rate (PEFR). This was due to mucous cells hypertrophy of the respiratory tract and bronchial epithelial cell damage by dust. This research purposed was to analyze the differences of peak expiratory flow rate in males between wood factory workers and office workers in Sukoharjo. This research was observational analytic with cross sectional approach and the sampling technique was using cluster sampling. Samples size was 60, divided into two groups consisting 30 males of wood factory workers and 30 males of office workers. Peak expiratory flow rate in both groups was measured by using a spirometer. Data were analyzed by unpaired t test. Based on the analysis of data obtained mean of PEFR on wood factory workers was 4.9209 L/sec, while the office workers was 5.9396 L/sec with p = 0.005. There were significant differences of peak expiratory flow rate in males between wood factory workers and office workers in Sukoharjo.